Digital selves and decision-making contexts: towards a research agenda. (10th June 2016) - Carton, Fergal; Brezillon, Patrick; Feller, Joseph
Abstract: The self is increasingly digitised, manifesting as a number of identities, accounts or profiles related to engagement with social, public and commercial services. These identities are multiplied across the civic, social, commercial, professional and personal contexts of their use, and the vulnerabilities of this atomised citizen are not well understood. This paper discusses the intellectual, organisational and social trends that underpin the emergence of the digital self. Building on this, the paper conceptualises the nature of the digital self and the value exchange and decision-making contexts in which it resides and acts. The conceptualisation is discussed in order to articulate a proposed agenda of research questions for the decision support systems, information systems, and related research communities.